The Quality Performance of Hotels and Restaurants in Ciwidey Destination Area - Asep Saepulloh; Ersy Ervina; Riza Taufiq (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The quality performance of hotels and restaurants in the Ciwidey tourist area experiences quite a few problems, which cause guests to experience dissatisfaction caused by poor service, poor cleanliness, and poor hotel and restaurant facilities, so consumers give much criticism directly and through social media, especially Google reviews. Therefore, this research aims to determine the quality development of hotels and restaurants in the Ciwidey tourist area and the level of guest satisfaction. This research method is a survey method with a quantitative approach, namely to determine the level of importance and performance satisfaction of tourists who have visited several hotels and restaurants in the Ciwidey area. The objects of this research are Ciwidey Valley Resort, Glamping Lakeside Situ Patenggang, and Puri Sakanti Nature Family Resort. The data collection technique in this research was distributing questionnaires to 120 respondents who had visited hotels and restaurants in the Ciwidey area. The data analysis technique in this study uses Importance-Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). The research results show that the performance of hotels and restaurants in the Ciwidey tourist area is very satisfactory, with an index of 86.48%. However, there is still a need to improve performance in several aspects to increase consumer satisfaction. The research results show that the performance of hotels and restaurants in the Ciwidey tourist area is very satisfactory, with an index of 86.48%. However, there is still a need to improve performance in several aspects to increase consumer satisfaction. The research results show that the performance of hotels and restaurants in the Ciwidey tourist area is very satisfactory, with an index of 86.48%. However, there is still a need to improve performance in several aspects to increase consumer satisfaction.